2015
DOI: 10.1016/j.ajpath.2015.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Initiates Infection Selectively from High-Level β1 Integrin–Expressing Cells in the Brain

Abstract: Cytomegalovirus (CMV) is a prevalent pathogen in intrauterine infections that causes congenital anomalies such as CMV encephalitis, which is characterized by the focal areas of reactive gliosis, reactive mononuclear cells, microglial nodules, and ventriculoencephalitis. To elucidate the mechanisms of CMV susceptibility in the developing brain, cell tropism and the infectious dynamics of CMV infection were investigated. We evaluated intraventricular and intravascular infections from the perspective of the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…We previously evaluated the differences in intraventricular and intravascular infection mouse models to investigate the relationship between distributions of MCMV particles and receptors in the neonatal mouse brain during the first viremic phase . Development in the neonatal mouse CNS is comparable to that in human fetuses at 17–20 weeks of gestation, and congenital HCMV infection is most often acquired during the early second trimester .…”
Section: Mcmv‐induced Brain Defects Are Caused By Disturbances In Neumentioning
confidence: 99%
See 1 more Smart Citation
“…We previously evaluated the differences in intraventricular and intravascular infection mouse models to investigate the relationship between distributions of MCMV particles and receptors in the neonatal mouse brain during the first viremic phase . Development in the neonatal mouse CNS is comparable to that in human fetuses at 17–20 weeks of gestation, and congenital HCMV infection is most often acquired during the early second trimester .…”
Section: Mcmv‐induced Brain Defects Are Caused By Disturbances In Neumentioning
confidence: 99%
“…h) at 12 hpi. CD31‐ cells and PDGFRβ‐positive cells express high levels of β1 integrin, which can trap MCMV particles during initial infection. A previous report confirmed that inhibition of β1 integrin by short hairpin RNA and functional blocking antibody significantly reduced MCMV infection.…”
Section: Mcmv‐induced Brain Defects Are Caused By Disturbances In Neumentioning
confidence: 99%
“…CMV neuroinvasiveness is mediated by a variety of entry factors, including integrins and EGFR, which are highly expressed by radial glia. Higher expression of these entry proteins determines the initial susceptible cell population (Kawasaki et al, 2015). …”
mentioning
confidence: 99%
“…Although unrelated to ZIKV, infection with CMV causes similar neurodevelopmental brain abnormalities [67,120]. The neuroinvasiveness of CMV is mediated by various entry factors, such as EGFR and integrins, which are particularly highly expressed in radial glia and neural stem/progenitor cells [121]. Higher expression of these entry proteins, particularly of β1 integrin in this case, determines the initial susceptible cell population in the brain.…”
Section: Vertical Transmission: Crossing the Placental Barriermentioning
confidence: 99%